The Effect of Sandblasting and Airless Spray Coating Mismatches on The Life of A Steel Building - Faradilla, Nur Siska; Santoso, Deri Teguh; Oleh, Oleh (Universitas Muhammadiyah Jakarta, 2024)
The quality of construction is paramount in ensuring the longevity of steel buildings. A primary cause of reduced lifespan in steel structures is the development of corrosion. To mitigate high corrosion rates, careful consideration must be given to the steel fabrication process, particularly coating. This study employs Fishbone, 4M+1E, and 5W+1H cause-and-effect analysis methods to examine the impact of the coating process on the lifespan of steel building structures. By identifying the root causes of various problem factors, the study offers recommendations and proper implementations to address these issues. Discrepancies in the coating process were identified, and several recommendations were proposed based on the root cause analysis. The findings aim to ensure the estimated lifespan of the steel piperack building structure by preventing premature corrosion. The results indicate that coating defects predominantly stem from human factors, and several repair recommendations are provided based on these findings.